EFFECTIVE PRACTICE STRATEGIES FOR OVERCOMING BURNOUT AMONG MUSIC STUDENTS - Shaarim, Siti Nur Anis; Tan , Bernard Yong Boon (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
In this era of increasing importance of mental health, reports and complaints about burnout is not uncommon, even amongst music students. This research explores the factors contributing to burnout and investigates effective music practice strategies to mitigate its impact. Focusing on undergraduate students at the Conservatory of Music, Universiti Teknologi MARA (UiTM), Shah Alam, the study adopted a qualitative approach to examine the challenges and coping mechanisms employed by students, through the use of interviews and content analysis. Semi-structured interviews were conducted with 10 participants to gain in-depth insights into the causes of burnout, including time management struggles, performance pressure, and ineffective practice routines. The findings revealed that burnout manifests through emotional exhaustion, physical fatigue, and decreased motivation, significantly affecting students’ academic and artistic performance. Moreover, through content analysis, the research highlighted several strategies to prevent and manage burnout. The role of support systems, including mentorship and institutional resources, was also emphasized in fostering a healthier and more sustainable learning environment. This study contributes to the growing body of research on burnout in music education by providing actionable recommendations for students, educators, and institutions. It underscores the importance of promoting mental well-being, effective practice strategies, and supportive environments to ensure the long-term success and resilience of music students.